Системно-впорядкована комбінація ціннісно-орієнтованих домінант формування природно-господарського простору - Микитенко, В.В. (Економіка природокористування і сталий розвиток, 2019)
Визначено й описано тріаду ціннісно-орієнтованих домінант формування та подальшого розвитку п’ятивимірної просторової системи управління природно-ресурсними активами в Україні. Їх розкрито за трьома площинами генерування багатокомпонентних здатностей до раціоналізації просторового управління, які розмежовано залежно від конститутивно-ключових властивостей управління природно-господарським простором держави та її регіонів. Групування виконано за напрямами, що обумовлені структурою та функціями системи, формують спроможність складної системи до самозбереження, характеризують тактику і стратегію поведінки просторової системи в контексті досягнення мети і розв’язання цільових завдань у сфері управління природно-ресурсними активами країни. The triad of value-oriented dominants of development, formation, and practical implementation into the economy, as well as further development in the resource limitations of the five-dimensional spatial system of natural resources assets management system in Ukraine were defined and described. They were disclosed according to three areas of generation of multi-component capacities for rationalization of spatial management, which are delineated according to constitutive and key properties of management of the natural and economic space of the state, its regions, and separate territories. Grouping and delineation were carried out in the directions which: are caused by the structure and target and specific functions of the system; form the capacity of a complex system for self-preservation; characterize the behavioural tactic and strategy of a spatial system for achievement of the objective and resolving the target tasks in the field of rationalization of the state’s natural resources assets management.
A set of model solutions was worked out and justified for calculation of the basic indices of its operation, namely: the relative organization of the spatial system architecture, structural and functional organization of its parameters, degree of uncertainty of the condition of a multi-dimensional management system, reliability of its operation as capacities for failure-free operation in various conditions of functioning, capacity of the spatial system and its five subsystems for self-preservation.
It was proved and confirmed that building up a new format of a spatial system of natural resources assets management with simultaneous incorporation of the provisions of the systemic, synergetic, structural and informational, and platform theoretical approaches protects rationalization of development and usage of the existing strategic potential of Ukraine and its regions based on the consequences of achievement of sustainable economy with resource limitations, accompanied with constant growth of socio-political threats and risks.